Microstructural non-linear finite-element analysis of rat myocardium with hydrogel biomaterial inclusions - Manack, Uzair (Department of Mechanical Engineering, 2025)
Hydrogel biomaterial injectate therapies have emerged as a promising treatment modality for myocardial infarction (MI). Studies conducted on small and large animal models have yielded positive results in improving cardiac function and reducing adverse ventricular remodelling post-MI. These therapies have also recently entered phase I and II human clinical trials, with limited positive results, but no significant adverse effects. Computational modelling has been used extensively to investigate the potential effects of hydrogel injec tate therapies, due to the risk-free and repeatable nature of these tests. Macroscale cardiac computational models are used to investigate the full-scale behaviour of the heart, while microscale models yield infor mation on the behaviour of the cardiac microstructure. In order to reduce computational expense, many existing studies make use of idealisations regarding the macroscale or microscale cardiac geometry, as well as the physical behaviour of both the cardiac tissue and hydrogel injectate. The aim of the current study was to develop a computational framework that reduced the need for idealisations of the cardiac microstructural geometry, evaluated the validity of the assumption that both the cardiac tissue and hy drogel injectate could be described as elastic solids, and provided a basis for extension to more complex descriptions of material behaviour. A realistic microstructural finite-element (FE) mesh was reconstructed from high-resolution confocal mi croscopy imaging data of rat myocardium. The reconstructed mesh did not necessitate idealisations of the cardiac tissue structure or the distribution of the hydrogel injectate. To investigate the mechan ical response of the microstructure, under the assumption that both the cardiac tissue and hydrogel behaved as elastic solids, an FE solver was developed using the open-source FE library deal.II. The solver was capable of implementing both isotropic and anisotropic hyperelastic material models, and applying thermodynamically-admissible boundary conditions to the microstructure. Suitable boundary conditions were derived from the results of an existing macroscale FE model of rat myocardium, and used to investigate the mechanical response of the microstructure under five possible loading scenarios. The results indicated that, under certain loading conditions, the observed stresses in the microstructure significantly exceeded reasonable elastic limits for the materials. This provides an indication that the assumption of elastic material behaviour is not always suitable when conducting in silico investigations of cardiac tissue and hydrogel injectate, and serves as a justification for the use of alternative descriptions of material behaviour. Furthermore, the framework was shown to be capable of implementing both static and time-dependent boundary conditions. This functionality provides the basis for the framework to be extended to more advanced models such as viscoelasticity and poroelasticity, which have been implemented in other studies using the deal.II library